The Impact of the Multi-Representational Discourse Learning Model and Student Involvement in Applying Multiculturalism Values - Muhamad Afandi; Reza Rachmadtullah; Atikah Syamsi (Universitas Pendidikan Ganesha, 2022)
Multiculturalism is the initial foundation in educating students to become citizens who can respect and appreciate diversity in Indonesia. Therefore, multicultural education is very important to be implemented in schools, especially elementary schools. This study aims to analyze the involvement of elementary school students in applying the values ​​of multiculturalism education with the Multi-Representational Discourse learning model. This study uses a mixed research method (mix-method). Data was collected through observation, interviews, and distributing questionnaires. The data collection instruments used were observation sheets, interview guidelines, and questionnaires. The data analysis process was carried out qualitatively and quantitatively. The results showed that the involvement of students in applying the value of multicultural education is the application of the value of learning to live in differences and mutual respect and honor. The application of multicultural values ​​with the Multi-Representation Discourse learning model invites to accept the differences that exist in fellow human beings as natural things (natural sunnatullah). In addition, multicultural education instills awareness in students about equality, justice, plurality, nationality, race, ethnicity, language, tradition, and respect for religion.